Management of familial Mediterranean fever by colchicine does not normalize the altered profile of microbial long chain fatty acids in the human metabolome - Ktsoyan, Zhanna; Beloborodova, Natalia V.; Sedrakyan, Anahit; Osipov, George; Khachatryan, Zaruhi; Manukyan, Gayane; Arakelova, Karine; Hovhannisyan, Alvard I.; Arakelyan, Arsen; Ghazaryan, Karine; Zakaryan, Magdalena; Aminov, Rustam (Frontiers in Cellular and Infection Microbiology, 2013)
In our previous works we established that in an autoinflammatory condition, familial Mediterranean fever, the gut microbial diversity is specifically restructured, which also results in the altered profiles of microbial long chain fatty acids (LCFAs) present in the systemic metabolome. The mainstream management of the disease is based on oral administration of colchicine to suppress clinical signs and extend remission periods and our aim was to determine whether this therapy normalizes the microbial LCFA profiles in the metabolome as well. Unexpectedly, the treatment does not normalize these profiles. Moreover, it results in the formation of new distinct microbial LCFA clusters, which are well separated from the corresponding values in healthy controls and FMF patients without the therapy. We hypothesize that the therapy alters the proinflammatory network specific for the disease, with the concomitant changes in gut microbiota and the corresponding microbial LCFAs in the metabolome.